PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN DENGAN WORD OF MOUTH SEBAGAI VARIABEL MODERASI DI BIRO PERJALANAN DEWANGGA LIL HAJJ WAL UMROH SURAKARTA - Heri, Sunarso & Sumaryanto (Universitas Slamet Riyadi, 2017)
Travel Agents Dewangga Lil Umrah Hajj Wal Surakarta in an effort to improvecustomer satisfaction to improve the quality of service is optimal. The purpose of thisstudy was to analyze the significance of the influence of service quality, price and wordof mouth on customer satisfaction. Analyzing the impact of service quality and price tocustomer satisfaction moderated word of mouth. This study uses survey method, the typeof data used quantitative and qualitative data, the data source used primary data andsecondary data. The population of consumers who use the services at the BureauDewangga Lil Umrah Hajj Wal Surakarta in 2016, amounting to 429 worshipers. Thenumber of samples in this study were 86 respondents, the sampling technique usesaccidental sampling. Data collection methods are used: questionnaires anddocumentation. Data analysis technique used to test the validity, reliability test, classicassumption test, multiple linear regression analysis and classical assumption. Inconclusion: There was a significant effect of service quality on customer satisfaction.There was a significant influence on the price of consumer satisfaction. There was asignificant effect of word of mouth on customer satisfaction. Word of mouth is notmoderate the impact of service quality to customer satisfaction. Word of mouth does notmoderate the effect of price on consumer satisfaction.Keywords: quality of service, price, word of mouth, customer satisfaction